1981
DOI: 10.1063/1.441448
|View full text |Cite
|
Sign up to set email alerts
|

Depolarized Rayleigh light scattering studies of concentrated aqueous nitrate solutions

Abstract: __________________________ SECURITY CLASSIFICATION OF THIS PAGE (ftem Date Entereod Continuation (Block #20)Vogel-Taman-Fulcher equation from which an ideal glass transition temperatur was derived. The viscosity dependence of T for both the Ca(NO ) and Zn(NO 3 ) solutions was found to be between that predicted by the classiaT StokesEinstein equation and that predicted using slip hydrodynamic boundary conditions. Nitrate rotation was found to be slower in Ca(N0 3 ) 2 solutions than in the corresponding Zn(N0 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These systems are indeed structurally different, as is reflected by their difference in viscosity, acidity, propensity for supercooling, and, in the case of the nitrate systems, differences in rotational relaxation times of the nitrate ions. 22 For example, concentrated aqueous ZnCl2 solutions are strongly acidic5 as are Zn(N03)2 solutions,23 whereas Ca(N03)2-4H20 is "neutral".6 Previously, ultrasonic compressibilities of aqueous nitrates and chlorides have been reported over a much more restricted range of concentration.24,25 It was observed that at corresponding salt concentrations ds increased for salts of increasing ionic radius, and in the case of other salts the reverse was ob- served. The only conclusion that could be reached was that number of important conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…These systems are indeed structurally different, as is reflected by their difference in viscosity, acidity, propensity for supercooling, and, in the case of the nitrate systems, differences in rotational relaxation times of the nitrate ions. 22 For example, concentrated aqueous ZnCl2 solutions are strongly acidic5 as are Zn(N03)2 solutions,23 whereas Ca(N03)2-4H20 is "neutral".6 Previously, ultrasonic compressibilities of aqueous nitrates and chlorides have been reported over a much more restricted range of concentration.24,25 It was observed that at corresponding salt concentrations ds increased for salts of increasing ionic radius, and in the case of other salts the reverse was ob- served. The only conclusion that could be reached was that number of important conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…Although Raman spectroscopic studies have been carried out extensively on metal nitrate solutions under ambient conditions, the Raman data have been scarcely presented at high temperatures and pressures. , For example, our knowledge of the temperature dependence of the rotational dynamics below 100 °C has been developed to a considerable extent; , however, that of the rotational dynamics of ions at higher temperatures and high pressures is lacking. Hence, little has been known about ion−ion and ion−water interactions, microstructures of ion hydration, and diffusional motion of salts on the molecular level in water in the high-temperature and high-pressure region.…”
Section: Introductionmentioning
confidence: 99%